The revised microRNA complement of Fasciola hepatica reveals a plethora of overlooked microRNAs and evidence for enrichment of immuno-regulatory microRNAs in extracellular vesicles. Issue 11 (September 2015) - Fromm, B.; Trelis, M.; Hackenberg, M.; Cantalapiedra, F.; Bernal, D.; Marcilla, A.
Graphical abstract: Highlights: Extracellular vesicles (EVs) from Fasciola hepatica contain microRNAs (miRNAs). 13 novel miRNAs have been identified. miRNAs related to immune regulation, tissue growth and cancer are enriched in F. hepatica EVs. Abstract: MicroRNAs (miRNAs) are gene regulators that have recently been shown to down-regulate the immune response via extracellular vesicles in the mammalian host of helminthic parasites. Using the miRNA prediction pipeline miRCandRef, we expanded the current miRNA set of the liver fluke Fasciola hepatica (Platyhelminthes, Trematoda) from 16 to 54 miRNAs (42 conserved and 13 novel). Comparing the cellular expression levels with extracellular vesicles, we found all miRNAs expressed and enriched for miRNAs with immuno-regulatory function, tissue growth and cancer. Our findings support the hypothesis that miRNAs are the molecular mediators of the previously demonstrated immune modulatory function of extracellular vesicles.